2020
DOI: 10.1039/d0nr03775c
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen doping and titanium vacancies synergistically promote CO2fixation in seawater

Abstract: N-Doped Ti3C2 MXenes with abundant titanium vacancies can be used in seawater with reasonable efficiency and good selectivity for CO2 electrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…The anodic reaction during discharge is the same as Equations (4)(5)(6)(7)(8). Overall reaction during discharge can be described as follows…”
Section: E θmentioning
confidence: 99%
See 1 more Smart Citation
“…The anodic reaction during discharge is the same as Equations (4)(5)(6)(7)(8). Overall reaction during discharge can be described as follows…”
Section: E θmentioning
confidence: 99%
“…Excessive fossil energy resource consumption and extreme CO 2 emission cause serious environmental problems and energy crises. [1][2][3][4][5][6][7][8][9][10][11][12][13] One of the feasible ways to address these issues is to develop renewable energy conversion and storage technologies, such as water/seawater splitting, fuel cells, metal-ion batteries, and rechargeable metal-air/CO 2 batteries. [14][15][16][17][18][19][20][21][22][23][24][25] In particular, rechargeable aqueous Zn-CO 2 batteries are gaining particular attention due to their unique feature of simultaneous fixing CO 2 and generating electrical energy, as well as the high theoretical energy density, abundant raw materials, and high safety.…”
Section: Introductionmentioning
confidence: 99%
“…Ti 2 CT x [188] Termination engineering -0.1 m KHCO 3 56.1 SA-Cu-MXene [105] Heteroatom doping GCE 0.1 m KHCO 3 59.1 NTC-VTi [189] Heteroatom doping/defect engineering CP Seawater 92 and charge transfer between the two components resulted in a significant OER performance and structural stability (Figure 13B-b,c). During the reaction, there was a good balance between adsorption and desorption, thereby enhancing .…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%
“…With their specific layered structure, 2D transition metal carbides and nitrides (MXenes) show high conductivity, high chemical stability, and multiple catalytic sites. Li et al calculated the catalytic activity of single-component MXenes by DFT, and the results showed that Cr 3 C 2 T x and Mo 3 C 2 T x are the best candidates for the electrochemical reduction of CO 2 to CH 4 [163] . These two materials favor the activation of CO 2 rather than H 2 O, resulting in highly efficient CO 2 electro-reduction and HER suppression.…”
Section: Other 2d Materialsmentioning
confidence: 99%